2012
DOI: 10.2478/v10078-012-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Low-Intensity Aerobic Training Improves Aerobic Capacity and Does Not Affect Psychomotor Performance in Professional Female Ballet Dancers

Abstract: We investigated whether 6-week low-intensity aerobic training program used as a supplement to regular dance practice might improve both the aerobic capacity and psychomotor performance in female ballet dancers. To assess their maximal oxygen uptake (VO2max) and anaerobic threshold (AT), the dancers performed a standard graded bicycle ergometer exercise test until volitional exhaustion prior to and after the supplementary training. At both these occasions, the psychomotor performance (assessed as multiple choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Therefore, it is likely that the mandatory wellness classes were responsible for this difference. Researchers have demonstrated improvement in aerobic fitness with supplemental training of varying lengths from 6 weeks to 1 year in preprofessional and professional modern and contemporary dancers 17,50,57 as well as professional ballet dancers, 58,59 thus supporting our findings. In contrast, other researchers have reported no change in aerobic fitness in preprofessional dancers with a 4-month conditioning program.…”
Section: Changes Over Time In Aerobic Fitnesssupporting
confidence: 87%
“…Therefore, it is likely that the mandatory wellness classes were responsible for this difference. Researchers have demonstrated improvement in aerobic fitness with supplemental training of varying lengths from 6 weeks to 1 year in preprofessional and professional modern and contemporary dancers 17,50,57 as well as professional ballet dancers, 58,59 thus supporting our findings. In contrast, other researchers have reported no change in aerobic fitness in preprofessional dancers with a 4-month conditioning program.…”
Section: Changes Over Time In Aerobic Fitnesssupporting
confidence: 87%
“…12 However, several studies have demonstrated that this is not the case. 10,13,15,21,25,38,53,57 For example, 12 weeks of non-specific supplementary aerobic (running, cycling, swimming) and strength training increased dancers' VO 2 max, strength, and flexibility with positive changes in dancers' body composition. 15 Angioi and coworkers 13 showed that 1 h circuit training plus vibratory training twice a week was more efficient than daily 1 h extra dance classes as supplementary training for contemporary dancers, increasing muscle power and resistance, aerobic capacity, and dance aesthetic competence.…”
Section: Thoughts On Supplementary Fitness Training For Dancersmentioning
confidence: 99%
“…Several other studies have used standard protocols for measuring dancers' VO 2 max and anaerobic threshold. 14,15,17,19,57,68,69 Even though there are nascent efforts in developing dance-specific testing protocols, 16,62,66 the lack of standardized methods for testing dancers of different styles in their familiar environment and pattern of movement may under-estimate dancers' fitness responses. It is widely acknowledged that testing anyone's cardiorespiratory fitness on a modality with which they are unfamiliar will always produce lower VO 2 peak/VO 2 max values, for example.…”
Section: Fitness Testing and Assessment For Dancementioning
confidence: 99%
“…The 48 selected studies included a total of 2,503 participants. Of these studies, 16 explored CRF in ballet dancers, 33-48 13 in contemporary or modern dancers, 49-61 and one in jazz dancers. 62 Nine studies included participants from two or more of these genres 63-71 and nine studies did not report the participants’ main genre.…”
Section: Resultsmentioning
confidence: 99%